PERBANDINGAN KARAKTERISTIK MARSHALL PADA ASPAL MODIFIKASI POLIMER PG70 DENGAN ASPAL MINYAK PEN 60-70 - Apteda, Prastama Errian; Royyan, Muhammad; Yuwanto , Hafizuddin Alfin Putra; Romadhon, Mohammad Hendrik Saputra; Putri, Ahna Mayhella (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Roads are land transportation infrastructure which includes all parts of the road including its complementary buildings which are designated for land vehicle traffic except railroads. In general, there are 2 types of road pavement structures in Indonesia, namely rigid pavement with the main material being concrete, then flexible pavement with the main material being a mixture of asphalt or Asphalt concrete. Asphalt mixture consists of several aggregates of a certain size and asphalt as a binder. Asphalt is generally made from the process of refining petroleum, but the longer the availability of petroleum will be depleted and increasingly expensive. This problem opened the idea of developing polymer modified asphalt by adding polymer ingredients to reduce the use of petroleum and increase the quality of asphalt. The Ministry of PUPR through the Director General of Highways applies rules regarding asphalt with PG70 polymer modification through the 2018 General Specifications. In this study a marshall test was carried out on PG70 polymer modified asphalt used for the Sidoarjo - Malang Road preservation project with pen 60-70 oil asphalt as a comparison. The results obtained by asphalt concrete with PG70 polymer modified asphalt have a greater marshall quotient value proving that PG70 polymer modified asphalt has better quality than asphalt concrete with pen 60/70 oil asphalt.